Effects of Glucocorticoids on the Inner Ear - Takeda, Taizo; Takeda, Setsuko; Kakigi, Akinobu (Frontiers in Surgery, 2021)
Hypothesis: Recently, several lines of evidence have suggested that the inner ear is under hormonal control. It is likely that steroids have some influence on the inner ear. Background: Many clinicians have been empirically using steroids for the treatment of diseases associated with endolymphatic hydrops. The theoretical grounds for this are not clear, and there have been a number of debates on the effectiveness of steroid treatment. Furthermore, there are few reports on histological observations of the influences of steroids on the cochlea. Method: Fifteen guinea pigs (30 ears) were divided into 3 groups. In the control group, physiological saline solution was administered intra-peritoneally for 3 days. In 2 steroid groups, 40 mg/kg/day of hydrocortisone or 4 mg/kg/day of dexamethasone was administered intra-peritoneally for 3 days. Extension of Reissner’s membrane and volume change of the scala media were checked 6 hours after the last administration. The degree of Reissner’s membrane extension and volumetric change of the scala media were quantitatively measured with the use of a video-digitizer. Results: We did not identify any distinct changes in the cochlea of the control group. In contrast, the extension of Reissner's membrane and endolymphatic hydrops were observed in the animals in the steroid groups. Statistical analysis revealed that Reissner’s membrane extended significantly in the steroid groups, and that the volume of the scala media also increased significantly. Conclusion: This is the first report to investigate the effects of systemic administration of glucocorticoids on guineapig cochlea. The extension of Reissner’s membrane and dilated endolymphatic space were evident in the steroid groups. However, the underlying mechanism of histological changes was not clear, marked care needs to be taken when administering steroids to patients with Meniere's disease whose histological feature is endolymphatic hydrops.